# Quadratic Equation has Only Two Roots

We will discuss that a quadratic equation has only two roots or in other words we can say that a quadratic equation cannot have more than two roots.

We will prove this one-by-one.

A quadratic equation has only two roots.

Proof:

Let us, consider the quadratic equation of the general form

ax$$^{2}$$ + bx + c = 0, (a ≠ 0) ............... (i)

Now divide each term by a (since, a ≠ 0), we get

x$$^{2}$$ + $$\frac{b}{a}$$x + $$\frac{c}{a}$$ = 0

⇒ x$$^{2}$$ + 2 * x * $$\frac{b}{2a}$$ + ($$\frac{b}{2a}$$)$$^{2}$$ – ($$\frac{b}{2a}$$)$$^{2}$$ + $$\frac{c}{a}$$ = 0

⇒ (x + $$\frac{b}{2a}$$)$$^{2}$$ - $$\frac{b^{2} - 4ac}{4a^{2}}$$ = 0

⇒ (x + $$\frac{b}{2a}$$)$$^{2}$$ – $$(\frac{\sqrt{b^{2} - 4ac}}{2a})^{2}$$ = 0

⇒ (x + $$\frac{b}{2a}$$ + $$\frac{\sqrt{b^{2} - 4ac}}{2a}$$)(x + $$\frac{b}{2a}$$ - $$\frac{\sqrt{b^{2} - 4ac}}{2a}$$) = 0

⇒ [x - $$(\frac{-b - \sqrt{b^{2} - 4ac}}{2a})$$][x - $$(\frac{-b + \sqrt{b^{2} - 4ac}}{2a})$$] = 0

⇒ (x - α)(x - β) = 0, where α = $$\frac{- b - \sqrt{b^{2} - 4ac}}{2a}$$ and β = $$\frac{- b + \sqrt{b^{2} - 4ac}}{2a}$$

Now we can clearly see that the equation ax$$^{2}$$ + bx + c = 0 reduces to (x - α)(x - β) = 0 and the equation ax$$^{2}$$ + bx + c = 0 is only satisfied by the values x = α and x = β.

Except α and β no other values of x satisfies the equation ax$$^{2}$$ + bx + c = 0.

Hence, we can say that the equation ax$$^{2}$$ + bx + c = 0 has two and only two roots.

Therefore, a quadratic equation has two and only two roots.

Solved example on quadratic equation:

Solve the quadratic equation x$$^{2}$$ - 4x + 13 = 0

Solution:

The given quadratic equation is x$$^{2}$$ - 4x + 13 = 0

Comparing the given equation with the general form of the quadratic equation ax$$^{2}$$ + bx  + c = 0, we get

a = 1, b = -4 and c = 13

Therefore, x = $$\frac{- b ± \sqrt{b^{2} - 4ac}}{2a}$$

⇒ x = $$\frac{- (-4) ± \sqrt{(-4)^{2} - 4(1)(13)}}{2(1)}$$

⇒ x = $$\frac{4 ± \sqrt{16 - 52}}{2}$$

⇒ x = $$\frac{4 ± \sqrt{-36}}{2}$$

⇒ x = $$\frac{4 ± 6i}{2}$$, [Since i = √-1]

⇒ x = 2 ± 3i

Hence, the given quadratic equation has two and only two roots.

The roots are 2 + 3i and 2 - 3i.

### New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.